POTENSI PASIR LOKAL TANJUNG BINTANG PADA ALUMINIUM SAND CASTING TERHADAP POROSITAS PRODUK HASIL COR ALUMINIUM - Yusup Hendronursito; Yogi Prayanda (JURNAL KAJIAN TEKNIK MESIN, 2016)
Green sand is one of the most important components in the process of metal casting. The sand in Indonesia region is varied level of subtlety, size of sand, and shape of sand. Green sand used in the process of metal casting is possible can affect the quality of casting product. This aims to determine the potential of Tanjung Bintang sand as green sand and the quality of the product in terms of porosity defects. The research was conducted by varying sand river from Tanjung Bintang and sand from Maringgai. Composition made varying  is 100%,75%, 50%, and 25% Tanjung Bintang sand compared Maringgai sand with bentonit and water is 10% and 5% constantly .The Examine of the green sand by SNI 15-0312-1989 among other water content, clay content, Grain Finnest Number (GFN), Shape of grain. The result said aluminium casting product with  50% Tanjung Bintang sand has the lowest value of porosity, 5.08% and the higher value with 75% composition of Tanjung Bintang sand, 6.98%.